Ablation properties of aluminum silicate ceramic fibers and calcium carbonate filled silicone rubber composites. Issue 11 (30th October 2014) - Zhou, Cheng; Yu, Lin; Luo, Wei; Chen, Yang; Zou, Huawei; Liang, Mei
ABSTRACT The ablative performance of aluminum silicate ceramic fiber (ASF) and calcium carbonate (CaCO3) filled silicone rubber composites prepared through a two‐roll mill was examined. The properties of the composites were investigated by thermogravimetry, thermal conductivity measurements, and oxyacetylene torch testing. After the material was burnt, the structure and composition of the char were analyzed by Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning electron microscopy (SEM). The results of the ablation test showed that the ablation resistance improved greatly in an appropriate filler scope. Combined with SEM, it was proven that a firm, dense, and thermal insulation layer, which formed on the composites surface during the oxyacetylene torch test, was a critical factor in determining the ablation properties. Thermogravimetric analysis revealed that the thermal stability of the composites was enhanced by the incorporation of ASF and CaCO3. The thermal conductivity measurements showed that the silicone rubber composites had a very low thermal conductivity ranging from 0.206 to 0.442 W m−1 K−1; this significantly prevented heat from transferring into the inner matrix at the beginning of the burning process. The proportion of 20/40 phr (ASF/CaCO3) was optimum for improving the ablation resistance of the silicone rubber composites. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41619.